Pengaruh Hubungan Body Shaming Dan Self-Esteem Dengan Mekanisme Koping Pada Usia Remaja Pertengahan Kelas X dan XI Di SEKOLAH MENENGAH ATAS “X” Bandung - Radho, Lucia Odilia; Tambunan, Dior Manta (Universitas Murni Teguh, 2025)
Adolescents experiencing Body Shaming cause changes in Self-Esteem that stimulateadaptive and maladaptive coping mechanisms. The purpose of this study was to determinethe relationship between body shaming and self-esteem with coping mechanisms in middleadolescence in grades X and XI at Senior High School “X” in Bandung. Quantitativeresearch method with cross-sectional survey. The sampling technique used purposivesampling with 171 respondents, the instrument used the G-Form Body Shaming,Rosenberg Self-Esteem Scale, and Ways of Coping questionnaire. Bivariate tests using ChiSquare and multivariate tests using Manova were used to analyze the data in this study.The results of this study using the chi square test showed that there was a relationshipbetween body shaming and coping mechanisms in middle adolescence in grades X and XIat Senior High School “X” in Bandung with a value of p = 0.001 (α <0.05), and there was arelationship between self-esteem and coping mechanisms in middle adolescence in gradesX and XI at Senior High School “X” in Bandung with a value of p = 0.001 (α <0.05). Manovatest shows a relationship between Body Shaming and Self-esteem with coping mechanismsin middle adolescence in grades X and XI at Senior High School “X” in Bandung with a valueof p = 0.000 (α <0.05). It can be concluded that there is a significant relationship betweenbody shaming and self-esteem with coping mechanisms in middle adolescence in gradesX and XI at Senior High School “X” in Bandung, schools are expected to provide a deeperunderstanding of the impact of body shaming and self-esteem and make efforts to preventcoping mechanisms, and handling cases of body shaming among middle adolescence atSenior High School “X” in Bandung. It is expected that further researchers will add researchvariables such as social support, academics, and family background to understand thefactors related to Body Shaming and Self Esteem.